Exploring the Demographics and Clinical Characteristics Related to the Expression of Angiotensin-Converting Enzyme 2, a Receptor of SARS-CoV-2 - Li, Shengjie; Han, Jianping; Zhang, Aiping; Han, Yi; Chen, Miaomiao; Liu, Zhenzhen; Shao, Mingxi; Cao, Wenjun (Frontiers in Medicine, 2020)
Objective: Coronavirus disease 2019 (COVID-19) was first reported in Wuhan, China, and has rapidly spread throughout the world. It has been reported that angiotensin-converting enzyme 2 (ACE2) is one of the major cellular entry receptors of COVID-19; thus, high ACE2 expression may increase susceptibility to infection. Therefore, we analyzed the expression of ACE2 in the blood to identify the individuals who may be susceptible to infection. Methods: In total, 229 subjects were enrolled in this study, and reverse transcription-quantitative polymerase chain reaction and ELISA assay was used to identify the level of ACE2 mRNA expression and ACE2 protein level in the blood. Demographic and clinical characteristics, including age, gender, weight, height, smoking habits, drinking habits, diabetes, and hypertension, were obtained using a face-to-face questionnaire. Independent Student’s t-test, Pearson’s linear correlation, logistic regression analysis, and multiple linear regression correlation were performed to assess the association between these factors and the expression of ACE2. Results: Higher level of ACE2 was observed in females, older subjects, subjects with hypertension, subjects with a cardiocerebrovascular disease, male smokers, and subjects with cancer (p<0.05) than in other subjects. Multiple linear regression analysis showed that there is a statistically significant correlation between being a female and ACE2 expression (β=0.550, p<0.001), between older age and ACE2 expression (β=0.197, p=0.003), between smoking and ACE2 expression (β=0.163, p=0.037), and between cancer and ACE2 expression (β=0.265, p<0.001). Logistic regression analysis revealed that female subjects (odds ratio [OR] = 2.255, 95% confidence interval [CI] = 1.770–2.872), subjects with hypertension (OR = 1.264, 95% CI = 1.075–1.486), subjects with a cardiocerebrovascular disease (OR = 1.271, 95% CI = 1.023–1.579), subjects with cancer (OR = 1.695, 95% CI = 1.253–2.293), and subjects above 60 years of age (OR = 3.097, 95% CI = 1.078–8.896) are at an increased risk of infection due to their high expression of ACE2. Conclusion: The level of ACE2 is higher in females, older subjects, smokers, and subjects with cancer than in other subjects, indicating that some of which are at higher risk for the severe forms of COVID-19 when they are exposed to the SARS-Cov-2.